The Moderating Influence of Government Policy on The Innovation Capability-Competitiveness Relationship in Food SMES - Stefanus Yufra Menahen Taneo; Melany Agustina; Sunday Noya (Journal of Technology Management & Innovation, 2023)
Food Small and Medium Enterprises (SMEs) in Indonesia have low competitiveness but receive less attention in innovation research. This study aims to analyze the relationship between innovation capability and competitiveness of food SMEs and to analyze the role of government policies in strengthening that relationship during the Covid-19 pandemic. Data were collected using an online questionnaire from food SMEs in Malang Regency. There were 162 returned and valid questionnaires for analysis. The results of the study prove that innovation capability was strongly related to the competitiveness of food SMEs. Government policies through training, credit, and marketing strengthen the relationship between product innovation and competitiveness, while it weakening the relationship between process innovation and the competitiveness of food SMEs. The Covid-19 pandemic is an externality factor that hinders resource mobility so that the production process is reduced which in turn has a negative impact on the competitiveness of food SMEs.